The awareness and use of outcome measures by South African physiotherapists - G. Inglis; M. Faure; A. Frieg (AOSIS, 2008)
Physiotherapists as well as otherhealth care providers a reunder pressure to provide evidence for the effectiveness of their interventions. Therefore it has become necessary to employ standardized androbust outcome measures in clinical practice. The objective of this study was to determine the awareness of and use of outcome measures (OM's)amongst physiotherapists in South Africa. A survey was conducted in2004 using a self-developed electronic questionnaire consisting of 18questions, both open- and closed-ended. A population-based sample consisting of 1102 members on the email address list of the South Africa Society of Physiotherapy (SASP) was used. Data analysis consisted ofboth descriptive statistics and qualitative analysis for the open-endedquestions. The response rate was 15.2% (n=168). Ninety one percent of respondents reported to have heard of OM's while 84% reported using OM's regularly. Impairment related measures were predominantly in use. The two main themes that emerged from therespondents'comments related to reasons forusing OM's were "effective clinical practice"(82%) and "evidence-basedpractice" (15%). Time constraints and lack of sufficient knowledge in the use of OM's, were cited as obstacles tousing OM's. These findings have implications forthe South African physiotherapy community in terms of education,continuous professional development (CPD) and future research in the usage frequency of OM's.